Erythropoietin in Friedreich ataxia. (17th July 2013) - Mariotti, Caterina; Nachbauer, Wolfgang; Panzeri, Marta; Poewe, Werner; Taroni, Franco; Boesch, Sylvia
Abstract: In Friedreich ataxia (FRDA), several candidate substances including erythropoietin (EPO) focus on increase in the amount of frataxin and aim to counteract the consequences of frataxin deficiency. Evidence for recombinant human erythropoietin (rHuEPO) in FRDA is based on in vitro studies using mouse neuronal cell lines, human fibroblasts, cardiomyocytes, and primary lymphocytes from FRDA patients or control subjects which showed a dose‐dependent increase of frataxin after incubation with different erythropoietins. The mechanism by which EPO induces frataxin increase remains to be elucidated, but may involve post‐transcriptional and/or post‐translational modifications of frataxin or alterations in frataxin half‐life and metabolism. In vivo data on rHuEPO's ability to increase frataxin in FRDA patients is contradictory as studies on the effect of EPO derivatives in FRDA differ in treatment regimen, sample size, and duration. Open‐label studies indicate for sustained frataxin increase, decrease of oxidative stress, and clinical improvement in FRDA patients after administration of rHuEPO. Two randomized controlled studies found acceptable safety and tolerability of EPO derivatives in FRDA. Secondary outcome measures, however, such as frataxin up‐regulation and clinical efficacy were not met. This review will focus on (i) pre‐clinical work on erythropoietins in FRDA and (ii) clinical studies in FRDA patients exposed to erythropoietins.